Cena Trimalchionis a Plato's Symposion - Subrt, Jiri (Aither, 2009)
Petronius' Cena Trimalchionis is first of all a display of culinary extravagancies and intellectual paltriness of the participants. However, most researchers agree that in some passages the Roman author parodies a sophisticated philosophical dialogue - Plato's Symposium. A passage like that is held to be the conversation of freedmen in chapters 41-47 whose discussion in the absence of their host has certain structural similarities with Plato's model. As the Italian researcher F. Bessone showed, in both works the conversation of the participants has the form of a convivial agon (despite not being formally proclaimed in Cena Trimalchionis), the number of speakers is identical and each speech is always a bit longer than the previous one. The question remains whether Petronius in his evocation of Plato's original stopped at the level of structural model or went further in caricaturing individual Plato's speakers. Some interpreters (for example, J. P. Bodel) find such similarities between individual characters no matter how vague they are. However, the question asked most frequently is whether Petronius' ``minisymposium'' has also its Socrates. According to some authors this role is divided between Trimalchion representing a kind of Anti-Socrates and the rhetor Agamemnon who, in turn, may be called a failing Socrates.In one of the characters appearing in Cena Trimalchionis is the Platonian model obvious, though, namely the stonemason Habinnas who is a little late for Trimalchion' s banquet. A number of circumstances of his entree reminds us of the character of Alcibiades from Symposium who is also an uninvited guest (akletos) disrupting the course of the banquet and redirecting the discussion in a new way. Both these belated comers are drunk returning from another banquet and bringing with them a woman; Habinnas his wife and Alcibiades a piper. However, despite the same details it is apparent that even here Petronius does not parody Alcibiades himself but rather makes use of his role in the symposium-like dialogue installing there a character that is the direct inversion of Plato's protagonist. The contrast between the original cast of that role and its degradation in the new context produces his satirical derision. The Roman author does not strive then for a ``mocking re-contextualization'' of his literary model but on the contrary he makes use of this literary model for a ``contextual mocking'' of representatives of a certain social milieu. As J. B. Conte showed this method is part of Petronius' broader satirical strategy and is also applied in the relation to other authoritative texts or genres whether it is a Homerian epic or a sentimental Greek novel.